All-optical scanning acoustic microscope - Sharples, Steve David (2003)
In this thesis a new instrument, the all-optical scanning acoustic microscope (O-SAM) is presented, it is a non contact scanning acoustic microscope (SAM) which uses lasers to both generate and detect surface acoustics waves (SAWs) The non contact nature of the O-SAM overcomes some difficulties associated with conventional SAMs because of the couplant and surface contact involved. This O-SAM also overcomes many of the problems associated with conventional laser ultrasound systems including those of sample damage and ablation, low signal to noise ratio and slow data acquisition. Furthermore, the instrument is adaptive enabling it to compensate to acoustic aberrations that can occur as a result of material microstructure. We believe this is a most significant feature that will greatly enhance its range of applications. This thesis examines some of the key technological developments required to develop the O-SAM, including the use of tailored optical generation pattern realised through the use of a spatial light modulator (SLM) and the development of a novel high speed analogue data acquisition system. This thesis presents the design and construction of the instrument and demonstrates its imaging capability on engineering materials using SAWs at 82 and 164MHz although the instrument is potentially capable of imaging at much higher frequencies. Images are presented on ceramic, steel and aluminium samples which demonstrate a range of contrast mechanisms and measurement techniques, including the interaction of the material with Rayleigh waves and Lamb modes for the purpose of defect detection and characterisation, and measurement of local variations in residual surface stress, changes in coating thickness, and plate thickness.